Ecological preferences and the carbon intensity of corporate investment - Michael Koetter; Felix Noth (Halle Institute for Economic Research (IWH), 2025)
Lowering carbon intensity in manufacturing is necessary to transform current production technologies. We test if local agents' preferences, revealed by vote shares for the Green party during local elections in Germany, relate to the carbon intensity of investments in production technologies. Our sample comprises all investment choices made by manufacturing establishments from 2005-2017. Our results suggest that ecological preferences correlate with significantly fewer carbon-intensive investment projects while investments stimulating growth and reducing carbon emissions increase by 14 percentage points. Both results are more distinct in federal states where the Green Party enjoys political power and local ecological preferences are high.
Keywords: D72; G31; G38; O13; 330; ecological preferences; elections; establishments' energy usage; investments